Effects of Sleep Disorders and Circadian Rhythm Changes on Male Reproductive Health: A Systematic Review and Meta-analysis - Zhong, Ou; Liao, Biyun; Wang, Jinyuan; Liu, Ke; Lei, Xiaocan; Hu, Linlin (Frontiers in Physiology, 2022)
Objectives The purpose of this study was to elucidate the relationship between sleep disorders and male reproductive health, and to explore the underlying mechanisms via a systematic review and meta-analysis Methods PubMed, Embase, The Cochrane library, Web of Science, Scopus databases were searched to collect clinical research on the effects of sleep disorders on male semen parameters from inception to February 24, 2022. RevMan 5.4 was used for meta-statistical analysis. Stata16 software was used to detect publication bias. Results The results of meta-analysis showed that sleep disorders were associated with reduced total sperm count (mean difference (MD) = -27.91, 95% CI = (-37.82, -18.01), p < 0.001), reduced sperm concentration (MD= -5.16, 95% CI = (-9.67, -0.65), p = 0.02), reduced progressive motility (MD = -2.94, 95% CI = (-5.28, -0.59), p = 0.01), and reduced normal morphology (MD = -0.52, 95% CI = (-0.80, -0.24), p < 0.001). However, there is no significant association between sleep disorders and semen volume/reproductive hormones. Further bioinformatics mining revealed that related clock genes (PER1, PER2, CRY2, NR1D1 and NPAS2) were down-regulated in non-obstructive azoospermia patients Conclusions In conclusion, current evidence suggests that sleep disorders have a negative impact on male reproductive health, and its underlying mechanism may be be related to circadian rhythm disorders. However, the relationship between sleep disorders and reproductive hormone levels has not been found. Due to the limited number and quality of included studies, the above findings need to be validated by more high-quality studies.